Strategi Promosi Perspektif Ekonomi Islam Guna Meningkatkan Jumlah Pengunjung di Wisata Edukasi “Kampung Nanas” Desa Palaan Kabupaten Malang - Rinawati, Ika; Chotib, Romadlon; Maya Sari, Ulil (Al-tsaman : Jurnal Ekonomi dan Keuangan Islam, 2022)
The tourist village "Kampung Nanas" which is still in the development stage requires a promotional strategy to increase the number of visitors. Promotion strategy in the perspective of Islamic economics is the right strategy because the promotion style is different from others. This study wants to provide ideas for the "Kampung Nanas" tourist village which has just been established and is trying to develop with all its limitations. The research method used is a qualitative research method with a case study approach. Data collection methods used are interviews, observation and documentation. The results show that the promotion strategy in the Islamic economy consists of 1. Advertising or advertising which is divided into the principle of monotheism, the principle of justice and the principle of trust, 2. Sales Promotion is by giving free entrance tickets. 3. Personal Selling is by socializing it to the Palaan community. Kampung Nanas Tourism Village has implemented promotions in accordance with Islamic teachings but needs to be maximized again because the promotions carried out are still very limited.